2010
DOI: 10.1021/bi1010877
|View full text |Cite
|
Sign up to set email alerts
|

Do Prokaryotes Have More Kinetically Stable Proteins Than Eukaryotic Organisms?

Abstract: Upon folding, some proteins become conformationally trapped, presumably to protect against aggregation or premature degradation. To probe the occurrence of this property, known as kinetic stability, we used a diagonal two-dimensional sodium dodecyl sulfate-polyacrylamide gel electrophoresis method to probe biologically diverse organisms. The results show that kinetic stability is prevalent in prokaryotes, especially thermophiles, but uncommon in eukaryotic organisms, thereby suggesting that this property might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 9 publications
(14 reference statements)
0
16
0
Order By: Relevance
“…38 The kinetic stability of proteins may be related to evolution. 40 The thermal stability of enzymes is a desirable feature for industrial applications that require high temperatures to develop products. 41 In species adapted to different thermal regimes, the kinetic properties of enzymes are typically correlated with environmental temperatures, but the correlation between adaptation temperature and enzyme thermal stability is less clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 The kinetic stability of proteins may be related to evolution. 40 The thermal stability of enzymes is a desirable feature for industrial applications that require high temperatures to develop products. 41 In species adapted to different thermal regimes, the kinetic properties of enzymes are typically correlated with environmental temperatures, but the correlation between adaptation temperature and enzyme thermal stability is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased rate of local and global unfolding of kinetically stable proteins accounts for their resistance to SDS-induced denaturation. 40 The inability of SDS to dissociate Cj-Cu, Zn SOD indicated that the enzyme was resistant to subunit dissociation (Fig. S6) in the presence of SDS 38,39 and is thus kinetically stable.…”
Section: Discussionmentioning
confidence: 99%
“…3. D2D SDS-PAGE assay for detecting KSPs ( (Xia, et al, 2007;Xia, Zhang, Solina, Barquera, & Colon, 2010). After 1D SDS-PAGE, the gel strip is excised and incubated in boiling SDS.…”
Section: Diagonal Two-dimensional (D2d) Sds-page Methods For Identifyimentioning
confidence: 99%
“…Therefore, we studied the cell lysates of the thermophilic bacteria Thermus thermophilus and Thermus aquaticus, and the archaea Sulfolobus acidocaldarius, which grow at optimal temperatures of 65, 70, and 80°C, respectively (Xia, Zhang, Solina, Barquera, & Colon, 2010) These thermophiles exhibited high number of SDS-resistant (i.e. KSPs) proteins (Fig.…”
Section: Monomeric and Alpha Helical Proteins Have Lower Probability mentioning
confidence: 99%
See 1 more Smart Citation